2022
DOI: 10.3390/nu14194127
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolomics Study on the Protective Role of Cocoa in Zucker Diabetic Rats via 1H-NMR-Based Approach

Abstract: Cocoa constitutes one of the richest sources of dietary flavonoids with demonstrated anti-diabetic potential. However, the metabolic impact of cocoa intake in a diabetic context remains unexplored. In this study, metabolomics tools have been used to investigate the potential metabolic changes induced by cocoa in type 2 diabetes (T2D). To this end, male Zucker diabetic fatty rats were fed on standard (ZDF) or 10% cocoa-rich diet (ZDF-C) from week 10 to 20 of life. Cocoa supplementation clearly decreased serum g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…For the elucidation of endogenous effects not necessarily involving the gut microbiota, NMR metabolomics analysis of urine can provide useful information. Fernández-Millán et al [32 ▪▪ ] conducted NMR-based metabolomics analyses of urine samples from diabetic rats that have received either a high-fat diet or a high-fat supplemented with 10% of cocoa. Multivariate data analysis identified 14 urinary metabolites to be important for discrimination of treatment groups, and subsequent pathway analysis suggested that these metabolite perturbations were indicative of modulations in butanoate metabolism, the synthesis and degradation of branched-chain amino acids and ketone bodies, which could be anticipated to be involved in underlying mechanisms behind the beneficial effects of cocoa on diabetes.…”
Section: Modulation Of Foodsmentioning
confidence: 99%
“…For the elucidation of endogenous effects not necessarily involving the gut microbiota, NMR metabolomics analysis of urine can provide useful information. Fernández-Millán et al [32 ▪▪ ] conducted NMR-based metabolomics analyses of urine samples from diabetic rats that have received either a high-fat diet or a high-fat supplemented with 10% of cocoa. Multivariate data analysis identified 14 urinary metabolites to be important for discrimination of treatment groups, and subsequent pathway analysis suggested that these metabolite perturbations were indicative of modulations in butanoate metabolism, the synthesis and degradation of branched-chain amino acids and ketone bodies, which could be anticipated to be involved in underlying mechanisms behind the beneficial effects of cocoa on diabetes.…”
Section: Modulation Of Foodsmentioning
confidence: 99%
“…A correlation analysis of pathways indicated major associations between some of the urine metabolites (mainly valine, leucine and isoleucine) and body weight, glycaemia, insulin sensitivity and glycated hemoglobin levels. The authors conclude that an untargeted metabolomics approach provides a clear metabolic fingerprint associated with chronic cocoa intake that can be used as a marker for the improvement of glucose homeostasis in a diabetic context [11].…”
mentioning
confidence: 98%
“…In a metabolomics approach on the protective role of cocoa in Zucker Diabetic Rats via 1H-NMR-based approach, Fernández-Millán and colleagues [11] identified 14 differential urinary metabolites in Zucker diabetic fatty rats fed with a 10% cocoa-rich diet for 10 weeks. A correlation analysis of pathways indicated major associations between some of the urine metabolites (mainly valine, leucine and isoleucine) and body weight, glycaemia, insulin sensitivity and glycated hemoglobin levels.…”
mentioning
confidence: 99%